2000
DOI: 10.1095/biolreprod62.4.1033
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Calcitonin Gene-Related Peptide Expression in Dorsal Root Ganglia of Rats by Female Sex Steroid Hormones1

Abstract: Calcitonin gene-related peptide (CGRP), a potent vasodilator primarily synthesized in dorsal root ganglia (DRG) neurons, has been shown to decrease vascular resistance and thus regulate blood flow to a variety of organs in rats. Serum CGRP levels in the human have been reported to increase with pregnancy and decrease postpartum. It has been suggested that female sex steroid hormones play a role in cardiovascular function, but the mechanisms are unknown. In this study, we examined the effects of estradiol-17bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 46 publications
6
61
0
Order By: Relevance
“…Numerous studies confirm the involvement of CGRP in the bone metabolism and pathophysiology of brain damage (4,5). Osteoblastic cells are equipped with receptors of CGRP, and cyclic adenosine monophosphate (cAMP) production in human osteoblastic cells can be enhanced by CGRP by as much as 30-50-fold (17), leading to changes in cell morphology and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies confirm the involvement of CGRP in the bone metabolism and pathophysiology of brain damage (4,5). Osteoblastic cells are equipped with receptors of CGRP, and cyclic adenosine monophosphate (cAMP) production in human osteoblastic cells can be enhanced by CGRP by as much as 30-50-fold (17), leading to changes in cell morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…CGRP is also capable of inhibiting bone resorption in vitro and inducing hypocalcemia in vivo (4). Moreover, during hematencephalon formation, the secretion of CGRP markedly increases (5), indicating that CGRP may be released directly by the injured brain tissue. The present study aimed to determine whether CGRP is one of the unidentified humoral factors that cause enhanced osteogenesis in patients with TBI and to identify the downstream pathway that is activated by increased CGRP expression.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the endogenous CGRP level in the circulation was significantly lower in OVX rats than in sham-operated rats, suggesting that ovarian hormone deficiency following ovariectomy decreases the plasma CGRP level. It has been reported that both estrogen and progesterone, which are ovarian hormones, stimulate CGRP peptide synthesis in dorsal root ganglia neurons through increasing CGRP mRNA (Gangula et al 2000a). Plasma CGRP levels in rats and humans have been reported to increase with pregnancy and decrease postpartum (Stevenson et al 1986, Saggese et al 1990, Gangula et al 2000b.…”
Section: Discussionmentioning
confidence: 99%
“…They further showed that the effects are inhibited by treatment with k252a, an inhibitor of the tyrosine kinase A (trkA), which has a high affinity for the NGF receptor, suggesting that the release of CGRP from the nerve endings is influenced by NGF. Furthermore, it has been reported that estrogen up-regulates expression of trkA mRNA in sensory neurons, where estrogen receptors and NGF receptor are co-localized (20,21). Together, these findings suggest that the number of VR-1 receptors may be decreased by attenuating the endogenous effect of NGF due to decrease in the activity of the trkA domain in the NGF receptor following estrogen deficiency with ovariectomy.…”
Section: +mentioning
confidence: 78%
“…On the other hand, regarding the involvement of estrogen on CGRP synthesis in dorsal root ganglia, it is suggested that CGRP mRNA expression is up-regulated (20) or contrarily down-regulated (22) by estrogen through its receptors, although estrogen receptors obviously exist in the dorsal root ganglia (22). In addition, our present result indicated that CGRP concentrations in dorsal root ganglia and the spinal cord and the mRNA expression in the dorsal root ganglia were not affected by estrogen deficiency and estrogen replacement in OVX rats.…”
Section: +mentioning
confidence: 99%